2006
DOI: 10.1002/nme.1879
|View full text |Cite
|
Sign up to set email alerts
|

Fast frequency sweep computations using a multi‐point Padé‐based reconstruction method and an efficient iterative solver

Abstract: SUMMARYProblems of the form Z( )u( ) = f( ), where Z is a given matrix, f is a given vector, and is a circular frequency or circular frequency-related parameter arise in many applications including computational structural and fluid dynamics, and computational acoustics and electromagnetics. The straightforward solution of such problems for fine increments of is computationally prohibitive, particularly when Z is a large-scale matrix. This paper discusses an alternative solution approach based on the efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 21 publications
(25 reference statements)
0
80
0
Order By: Relevance
“…Thus, the Padé-reconstructed solutions are established with m f = m σ = 4, with the constraint n i = m i + 1 for the denominator truncations. This constraint echoes the choice made for univariate Padé approximants in recent publications [4,5]. Note that the choice of the best truncation orders is an important and intricate step of the method, which is still given much attention in the Padé approximants community.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, the Padé-reconstructed solutions are established with m f = m σ = 4, with the constraint n i = m i + 1 for the denominator truncations. This constraint echoes the choice made for univariate Padé approximants in recent publications [4,5]. Note that the choice of the best truncation orders is an important and intricate step of the method, which is still given much attention in the Padé approximants community.…”
Section: Resultsmentioning
confidence: 83%
“…In analogy to previous contributions for univariate FE problems [4,5], the partial derivatives of the solution vector can be calculated recursively by a method based on the use of the general Leibniz rule for multiple variables. For two independent variables, and applied to the left hand side of Eq.…”
Section: Solution Vector Partial Derivatives For the Bivariate Solutimentioning
confidence: 99%
See 1 more Smart Citation
“…It is said to be a multi-point Padé Approximation [13] if P frequency points are defined and interpolated in the frequency interval of interest, ∆ ω , where each frequency is denoted by ω p with p = 1, 2, 3, ..., P , using…”
Section: Multi-padé Approximationmentioning
confidence: 99%
“…It has been shown that such a rational function can be accurately and efficiently approximated by an appropriate Padé expansion [5,6,7,4,10,1]. The numerical algorithm proposed in this paper for identifying the eigenvalues missed in a given range of interest builds on the aforementioned observations.…”
Section: Introductionmentioning
confidence: 99%